2016
DOI: 10.1017/s1473550416000434
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial growth tolerance to concentrations of chlorate and perchlorate salts relevant to Mars

Abstract: The Phoenix lander at Mars polar cap found appreciable levels of (per)chlorate salts, a mixture of perchlorate and chlorate salts of Ca, Fe, Mg and Na at levels of ~0.6% in regolith. These salts are highly hygroscopic and can form saturated brines through deliquescence, likely producing aqueous solutions with very low freezing points on Mars. To support planetary protection efforts, we have measured bacterial growth tolerance to (per)chlorate salts. Existing bacterial isolates from the Great Salt Plains of Okl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 56 publications
2
38
1
Order By: Relevance
“…For example, Oren et al (2014) found no effect of 0.2 M perchlorate on aerobic growth by several archaeal extreme halophiles, but noted partial to substantial inhibition at higher concentrations (0.4–0.6 M). Limited tolerance of 1 M perchlorate has been also reported for several bacterial isolates during aerobic growth assays ( Al Soudi et al, 2017 ), but those assays were conducted at much higher water potentials (-1.4 to -5.6 MPa, e.g., moderate salt concentrations and less physiological water stress) than used in this study (-19 MPa). Thus, the ability to oxidize CO during substantial water stress (i.e., lower water potentials) and simultaneously high concentrations of a potent chaotrope [perchlorate ( Cray et al, 2013 )] is unprecedented.…”
Section: Resultsmentioning
confidence: 81%
“…For example, Oren et al (2014) found no effect of 0.2 M perchlorate on aerobic growth by several archaeal extreme halophiles, but noted partial to substantial inhibition at higher concentrations (0.4–0.6 M). Limited tolerance of 1 M perchlorate has been also reported for several bacterial isolates during aerobic growth assays ( Al Soudi et al, 2017 ), but those assays were conducted at much higher water potentials (-1.4 to -5.6 MPa, e.g., moderate salt concentrations and less physiological water stress) than used in this study (-19 MPa). Thus, the ability to oxidize CO during substantial water stress (i.e., lower water potentials) and simultaneously high concentrations of a potent chaotrope [perchlorate ( Cray et al, 2013 )] is unprecedented.…”
Section: Resultsmentioning
confidence: 81%
“…Hygroscopic sulfate salts have also been detected in martian soils (Smith et al , 2014 ). Through deliquescence, these salts can produce saturated brines with very low freezing points (Davila et al , 2010 ; Al Soudi et al , 2017 ). If the hygroscopic sulfate salts contain radionuclides, this may produce another habitable microenvironment for microorganisms that obtain energy from sulfate reduction by H 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is shown that econiches with liquid water and positive temperatures can occur on the current Mars [88,[90][91][92][93]. Terrestrial microorganisms can grow under combined low pressure, temperature, and anoxic atmosphere conditions [94], it can withstand the impact of Martian salts and strong oxidizers [95][96][97][98], and can survive in subzero brines [99,100]. If even slow repairing of cells' damages occurs, it can be of great effect during geological time.…”
Section: Implications For Habitability Assessmentmentioning
confidence: 99%